Performance of RAP-Based HRS-WC Mixtures Using Natural Rubber as Rejuvenator - I Made Agus Ariawan; Andre Wisnu kusuma; I Nyoman Arya Thanaya (Universitas Pendidikan Nasional, 2026)
The growing demand for road pavement materials has encouraged the use of Reclaimed Asphalt Pavement (RAP) as a sustainable alternative. However, binder aging in RAP increases mixture stiffness, requiring rejuvenating agents to restore asphalt properties. This study aims to analyze the effect of Natural Rubber (NR) as a rejuvenating agent in RAP-based Hot Rolled Sheet-Wearing Course (HRS-WC) mixtures under unaged, Short-Term Oven Aging (STOA), and Long-Term Oven Aging (LTOA) conditions. The mixtures were designed using the Marshall method in accordance with RSNI M-01-2003, with NR contents of 0%, 5%, and 10% by weight of RAP asphalt. Performance evaluation included stiffness, deformation resistance, and fatigue resistance tests. The results indicate that NR affects the characteristics of RAP-based HRS-WC mixtures. The Indirect Tensile Stiffness Modulus (ITSM) decreases with increasing NR content, indicating improved flexibility and elasticity. However, stiffness increases after STOA and LTOA due to binder aging. The 10% NR mixture showed the best deformation resistance, with the lowest creep slope of 0.1284 under STOA. It demonstrated the highest fatigue resistance, achieving 10,311, 2,111, and 611 cycles to failure under unaged, STOA, and LTOA conditions, respectively. These findings demonstrate NR's potential as a rejuvenating agent for improving RAP-based HRS-WC performance and durability.